PENERAPAN MODEL KOOPERATIF TYPE TALKING STICK TERHADAP HASIL BELAJAR SISWA PADA MATERI MAKNA NORMA DALAM KEHIDUPAN KU DI KELAS V SDI PERUMNAS 1 KOTA KUPANG - Osingmahi, Diana Margarita; Koroh, Taty Rosiana; Kota, Martha Khristina (Journal of Character and ELementary Education, 2025)
This research aims to improve student learning outcomes about the Meaning of Norms in My Life through a cooperative learning model of talking stick type in grade V of SD Inpres Perumnas 1 Kupang City. With 20 students, 9 male students and 11 female students. The research method used is data collection techniques, namely observation and tests. The analysis technique used is to find the average of the class. This research was carried out based on a classroom action research procedure with 2 cycles.This research was conducted at SD Inpres Perumnas 1, with the results of the study showing that in the first cycle of learning from 20 students, the ones who completed were 12 students with a percentage (60%) while those who did not complete were 8 students with a percentage (40%). Furthermore, in the second cycle of 20 students, 18 students completed with a percentage (90%) while students who did not complete as many as 2 students with a percentage (10%). The application of the cooperative model of the talking stick type encourages students to have the ability to express opinions and ask questions, as well as have the knowledge to answer questions both individually and in groups. According to the results of the research on the learning outcomes above, it is known that the application of the cooperative model of the talking stick type to student learning outcomes on the material of the meaning of norms in my life has achieved significant results and has been proven to improve the learning outcomes of grade V students of SD Inpres Perumnas 1.